Selected Proteins and Enzymatic Analysis of Follicular Fluid of Indigenous Pig at Different Developmental Stages of Ovarian Follicle: a Quantitative Study - Chakraborty, D.; Ray, S. K.; Datta, U.; Mukhopadhayay, S. K.; Ganguly, S. (International Journal of Bio-resource and Stress Management, 2023)
In the present study, characteristics of porcine follicular fluid (FF) harvested from different sized ovarian follicles and developmental competences of enclosed oocytes in relation to their sizes were investigated. It has been observed that some protein and enzyme components of FF like lipase, amylase and CPK increased in concentration as the follicles increased in size, while some other components like AFP, ACP and ALP were found to be decreasing order with increase in follicular size. A few unexplored components like AFP and Li have been studied here in the present study. Moreover, presence of amylase, lipase and CPK in FF and their concentrations have also been detected in the porcine FF for the first time in this study.